Arthrographis kalrae Keratitis Complicated by Endophthalmitis: A Case Report With Literature Review. Issue 6 (November 2020) - Ting, Darren Shu Jeng; Mckenna, Michael; Sadiq, Salman Naveed; Martin, Jessica; Mudhar, Hardeep S.; Meeney, Adam; Patel, Trushar
Abstract : Objectives: To report the first case of Arthrographis kalrae keratitis complicated by endophthalmitis in the UK and to review the current literature. Methods: A case report with literature review. Results: A 65-year-old male patient, with a background of treated B-cell lymphoma and herpes simplex virus-related neurotrophic keratopathy, presented with a large infiltrative corneal ulcer in the right eye. The patient was immediately commenced on empirical antifungal treatment in view of the clinical suspicion of fungal keratitis (FK). The initial corneal scrape identified the organism as nonspecific "mold, " and the identity of A. kalrae was subsequently confirmed using matrix-assisted laser/desorption ionization-time of flight-mass spectrometry (MALDI-TOF-MS). During the clinical course, the patient received topical, intrastromal, intracameral, and systemic antifungal treatment, repeat therapeutic corneal cross-linking treatment, and three penetrating keratoplasties. Although a temporary improvement was achieved with therapeutic corneal cross-linking treatment, the FK progressed relentlessly and was ultimately complicated by an endophthalmitis despite maximum medical and surgical treatment, eventuating in an enucleation. Conclusions: A. kalrae keratitis is an exceptionally rare clinical entity that poses significant therapeutic challenges. MALDI-TOF-MS serves as a useful diagnostic technique in identifying this rare organism. Although the literature suggested that A. kalrae keratitis may sometimes be controlled with antifungal medical treatment alone, this approach was proven to be futile in our immunocompromised patient with pre-existing neurotrophic keratopathy, suggesting that early surgical intervention such as therapeutic keratoplasty may be required in these cases.